Çubuk Yöresi Alevi Köylerinde Yaşayan Alevilerin İnanç Pratikleri Üzerine Bir Araştırma - Türk, Sezai; Güven, Ahmet; İşi, Ayşe (Journal of Alevism-Bektashism Studies, 2012)
in this study which is conducted within the scope of the Çubuk district of Ankara province, the identification and analysis of cultural beliefs and rituals in the villages of Alevi and Bektashi in Çubuk are aimed. The survey method was used for this purpose. in the field research questionaire technique was used in the surveyas a means of data collection technique , and the observation units were reached by the help of village chiefs, the Alevi associations and Cem houses. in the study conducted in the villages of the town of Çubuk, Alevi Bektashi religious practices were asked the people of the village and during the study data and materials collected was obtained and analyzed in a particular category Alevis living in the villages of Çubuk region primarily as a result of the analysis of demographic characteristics and then cultural beliefs and practices related to Alevism then evaluated. Approximately 26% of the Alevis who are member of Ocakzadeler , 29% did not know that the members of which branch were. 89% of the Alevi culture sacrifised at least one of the victims, 67% of the Alevi culture were kept at least one of fast. Alevis living in villages in the Alevi faith related to Alevism rod region, culture and traditions carried on nowadays have been identified.
Keywords: Alevisim; Alevis of Çubuk Region; Sacrifice in Alevism; Fast in Alevism; Cem; Whirl